(untitled) (Fiep Bulletin - online, 2014)
Temporal organization of arm movements was assessed in expert basketball players while performing an accurate throw (free throw). Kinematic analysis indicated that the predominant sequence of peak acceleration was the elbow extension first, followed by wrist flexion, and shoulder flexion last, at relative times of 0.55, 0.76, and 0.88, respectively. These results suggest that in proficient throwing performance organization propulsive forces are specified in anticipation to the future arm position determining the ball’s release angle.